Decomposition of Demographic Effects on the German Pension System - Robert Fenge; François Peglow (Center for Economic Studies and ifo Institute (CESifo), 2017)
The paper analyses the impact of demographic developments on the German pension system until the year 2060. The projections are simulated for a range of assumptions on the latest demographic trends and on the labour market and comprise the latest pension legislation. As a central innovation we present a decomposition approach which allows to identify the isolated effects of mortality, fertility and migration developments on the dynamics of the German pension system. We show that the past population structure - driven by past fertility changes - and future mortality improvements will be the most important factors shaping the development of the German pension system. The results have a number of implications for effective and sustainable pension reforms.
Keywords: H55; 330; population ageing; German pension system; labour market